Sikap guru mengenai intervensi aktivitas fisik dan diet pada siswa obesitas di sekolah dasar - Makalew, Mahesa M. T.; Ratag, Gustaaf A. E.; Pandelaki, August J. (UNIVERSITAS SAM RATULANGI, 2017)
Objective: This study aims to determine the attitude of the teachers in the intervention of physical activity and dietary interventions on obesity in elementary school students. Methods: This study used a mixed methods research type of research that combines quantitative and qualitative. Results and Conclusion: The results showed that the informant Knowledge is still lacking because the informant did not fully understand the definition of obesity, the characteristics of children who are obese and the impact of obesity on the health of children. Keywords: teachers attitudes, physical intervention, dietary intervention, obese students